Shock Index Thresholds to Predict Adverse Outcomes in Maternal Hemorrhage and Sepsis: A Prospective Cohort Study. Issue 2 (June 2020) - Nathan, H.L.; Seed, P.T.; Hezelgrave, N.L.; De Greeff, A.; Lawley, E.; Anthony, J.; Steyn, W.; Hall, D.R.; Chappell, L.C.; Shennan, A.H.
Abstract : ( Acta Obstet Gynecol Scand . 2019;98:1178–1186) Almost half of annual maternal deaths can be attributed to postpartum hemorrhage (PPH), maternal sepsis, and abortion complications. Most of these deaths are avoidable with early identification of hemodynamic compromise, but many care providers lack the adequate training to respond properly to abnormal blood pressure (BP) and heart rate (HR) measurements. The ratio of HR to systolic BP, called the shock index (SI), is believed to be an early indicator of life-threatening adverse outcomes; SI has predicted medical events more consistently than other vital signs in PPH retrospective cohorts. While experts have proposed the use of SI measurement thresholds as early warning signs, more research is needed in PPH and maternal sepsis populations. These investigators conducted their study to determine whether SI can consistently predict adverse outcomes in PPH and maternal sepsis cases, and also observe if previously determined SI thresholds are adequate.